2010
DOI: 10.1007/s00468-010-0493-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of gold nanoparticles by various leaf fractions of Semecarpus anacardium L. tree

Abstract: Gold nanoparticles (NPs) were synthesized using Semecarpus anacardium leaf extracts in water and the green biomass. Extract prepared at ambient condition by crushing the leaves in deionized water is identified as 'green extract', and that by boiling the leaf pieces as 'boiled extract'. The mass remaining after separating the 'green extract' is identified as 'green biomass'. These components triggered rapid reduction of Au(III) to Au (0) in HAuCl 4 solution indicating the natural ability of the leaves of S. ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In the present work, synthesis of nanoparticles also increases with time. Similarly, in our earlier report , the increased formation of nanoparticles by Semecarpus leaves was studied with respect to the time scale.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In the present work, synthesis of nanoparticles also increases with time. Similarly, in our earlier report , the increased formation of nanoparticles by Semecarpus leaves was studied with respect to the time scale.…”
Section: Resultsmentioning
confidence: 62%
“…The other green process for the synthesis of nanoparticles by various plant extracts has been well studied by Song and Kim and Song et al in plants such as Diopyros, Magnolia, Ginkgo, Platanus, and Pinus; Shankar et al , reported on Azadirachta indica and Lemongrass; Ankanna et al used Boswellia ovalifoliolata ; and Rajasekharreddy et al used Jatropha curcas L. In Syzygium cumini , extracts of dry powders of leaf and seeds were used for the synthesis of silver nanoparticles . In our earlier report , we demonstrated the synthesis of gold nanoparticles (GNPs) by using various leaf fractions of Semecarpus anacardium L.…”
Section: Introductionmentioning
confidence: 99%
“…Biological synthesis of nanoparticles using microorganisms (Klaus et al 1999;Konishi et al 2007;Nair and Pradeep 2002), enzyme (Willner et al 2006) and plants or plant extracts (Shankar et al 2004;Raju et al 2011Raju et al , 2012Raju et al , 2013a has been suggested as possible alternative ecofriendly method.…”
Section: Introductionmentioning
confidence: 99%
“…Almost any imaginable reagent has been demonstrated to be suited to produce AuNPs when added to aqueous solutions of tetrachloroaurate(III) in the above described chemical synthesis. Examples of reduction/stabilizing agents in recently published "green" synthesis [14,15] protocols are fruit (banana, [16] pear, [17] citrus fruits), [18] vegetables (cabbage, [19] horse gram), [20] flowers (roses [21] , daisies), [22] plant leaves [23] (almond, [24] mahogany, [25] mango, [26] olive, [27] semecarpus, [28] callistemon, [29] curry tree, [30] memecylon), [31] (culinary) herbs, [32][33][34][35] spices (clove buds, [36] saffron), [37] plant roots (ginseng, [38] ginger), [39] natural gum [40,41] and propolis, [42] bacteria, [43,44] fungi, [45][46][47][48] algae, [49] peptides [50] and proteins and enzymes, [51,52] gripe water, [53] butterfly wings, [54] human skin [55] and hair. [56] The reduction of gold ions to AuNPs also works in aerosols …”
Section: Aumentioning
confidence: 99%